1979
DOI: 10.1029/rs014i002p00309
|View full text |Cite
|
Sign up to set email alerts
|

Absorption around the electron cyclotron frequency in a thermal plasma of finite density

Abstract: Cyclotron absorption around the electron cyclotron frequency in a weakly relativistic plasma of finite density in thermal equilibrium is considered for both perpendicular and quasi‐perpendicular propagation. A comprehensive analysis which includes thermal effects together with finite density corrections is given and the resulting scaling of the absorption of the extraordinary and the ordinary modes is examined. The line profiles are discussed and the optical thicknesses of a typical tokamak plasma are evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…for frequencies around the cyclotron harmonics, or [5] <\ (5) (v t = (2kBT e /m 0 ) 1/2 , co c = qB/m 0 , and m 0 is the electron rest mass) for frequencies near the fundamental cyclotron frequency, for near-perpendicular emission. (For the Doppler regime, where N| >vt/c, Eq.…”
Section: The Optical Constantsmentioning
confidence: 99%
“…for frequencies around the cyclotron harmonics, or [5] <\ (5) (v t = (2kBT e /m 0 ) 1/2 , co c = qB/m 0 , and m 0 is the electron rest mass) for frequencies near the fundamental cyclotron frequency, for near-perpendicular emission. (For the Doppler regime, where N| >vt/c, Eq.…”
Section: The Optical Constantsmentioning
confidence: 99%
“…In addition, since a N p ~ g 2 , the absorption coefficient is proportional to g" 2 , and the scaling is inverted from the low-density result. This has been discussed by Fidone et al [6] and by Bornatici and Engelmann [7,8].…”
Section: The First-harmonic Extraordinary Modementioning
confidence: 80%
“…where /u = m o c 2 /kT e , this resonant denominator can no longer be approximated by to -£co B , and a relativistically correct treatment is necessary [7]. Dnestrovskii, et al [4] have shown that the values of the dielectric-tensor elements differ from those calculated by the non-relativistic approach only at the first harmonic (both modes) and the secondharmonic extraordinary mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonlinear effects associated with relativistic electron-mass variation and the pondermotive force in unmagnetized as well as magnetized plasmas have been studied by many authors (Stenflo 1976;Kotsarenko 1977;Stenflo & Tsintsadze 1979;Nishikawa et al 1980;Papuashvili et al 1980Papuashvili et al , 1985Tsintsadze et al 1980;Berezhiani & Tskhakaya 1981;Shukla et al 1986). Furthermore, linear absorption and the dispersion relation in a relativistic magnetized plasma (Trubnikov 1959;Bornatici & Engelmann 1979;Cairns & Lashmore-Davies 1982) and quasi-linear and nonlinear wave-wave interactions in a magnetized plasma containing a relativistic electron beam or intermixed by energetic losscone electrons (Aizatskii 1980;Miroshnichenko 1980;Okazaki & Kato 1980;Ziebell & Yoon 1995) have been analysed theoretically, taking relativistic effects into account. In particular, it is very important to study kinetic effects due to nonlinear wave phenomena in a relativistic plasma, since these are related to relativistic electron beam acceleration (Sugaya 1993(Sugaya , 1994 and to energy and momentum transport in a fusion plasma.…”
Section: Introductionmentioning
confidence: 99%